2019
DOI: 10.1186/s12979-019-0163-x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of CLL-associated stereotypic B cell receptors in the normal BCR repertoire from healthy individuals increases with age

Abstract: Background Aging is known to induce immunosenescence, resulting in alterations in both the innate and adaptive immune system. Here we evaluated the effects of aging on B cell subsets in peripheral blood of 155 immunologically healthy individuals in four age categories (range 20-95y) via multi-parameter flow cytometry. Furthermore, we studied the naive and antigen-experienced B cell receptor (BCR) repertoire of different age groups and compared it to the clonal BCR repertoire of chronic lymphocytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
2
15
2
Order By: Relevance
“…In accordance with previous studies, our results demonstrated that the number of both T cells (including CD4 + and CD8 + T cells) and B cells gradually decreased with increasing age [12,13]. Previous studies have also shown that the diversity of B cell phenotype is decreased in elderly people, which results in decreased protective effect of vaccination in them compared with young people [12,[14][15][16]. These data suggest that the number of adaptive immune cells gradually decreases during life.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies, our results demonstrated that the number of both T cells (including CD4 + and CD8 + T cells) and B cells gradually decreased with increasing age [12,13]. Previous studies have also shown that the diversity of B cell phenotype is decreased in elderly people, which results in decreased protective effect of vaccination in them compared with young people [12,[14][15][16]. These data suggest that the number of adaptive immune cells gradually decreases during life.…”
Section: Discussionsupporting
confidence: 92%
“…It was found that the relative frequency and total number of B cells will decrease with age. Plasma blasts, memory cells and transitional B cells are decreased in patients older than 70 years [28]. Lymphocytes and their subsets [including NK cells (CD56+), B cells (CD19+) and T cells (CD3+)] are mainly responsible for regulating host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…[24]Total numbers and relative frequencies of B cells were found to decline upon aging, with reductions in transitional B cells, memory cell types, and plasma blasts in the 70 + y group. [25]Lymphocytes and subsets including T(CD3+) cell, B(CD19+) cell and NK(CD56+) cell are mainly responsible for host immune regulation, T cells play a dominant role in promoting or sustaining in ammatory processes through inducing proin ammatory cytokines production. [23,[26][27][28][29]Activated Th1 cells, one subtype of CD4+ effector T cell, could trigger phagocyte-Previous research found that in COVID-19 patients higher expression of proin ammatory cytokines and chemokines, especially in the severe cases, the consumption of CD4+ and CD8+ T cells, and the decrease of regulatory T cells, might result in aggravated in ammatory responses, the production of cytokine storm and make damaged tissue worse.…”
Section: Discussionmentioning
confidence: 99%